Report Analysis of Cash Flows in the Regional Government of Boalemo Regency - Iswan Alam; Titin Dunggio; Sukrianto (LP2M Universitas Bina Mandiri Gorontalo, 2021)
The aim to be achieved in this research is to know in-depth about the results of the analysis of cash flow reports in the local government of Boalemo Regency. In this study, researchers used quantitative research types. From the research population above, samples were taken from the 2017-2018 cash flow statement in the Regional Government of Boalemo Regency. The method used in this paper is descriptive quantitative using cash flow ratios. The results showed that the analysis of aruskas reports in the local government of Boalemo district was seen from: 1) from the results of the analysis of the Operational Cash Flow Ratio data after the analysis there was an increase of 5.5%, this explains that the Regional Government of Boalemo Regency has a good financial performance with an increase in the average increase; 2) from the results of the data analysis of the investment cash flow ratio, after the analysis was carried out there was an increase of 4.9%. Looking at the data shows that the average increase is good from 2017 to 2018. So that the Regional Government of Boalemo Regency is able to manage related cash management aimed at acquiring and disposing of fixed assets and other investments in cash; 3) from the data analysis, the Funding Cash Flow Ratio after the analysis is down to 4.6%. In financing cash flow reflects the demand and cash disbursements related to long-term loans; 4) from the results of the analysis of the Transitoris Cash Flow Ratio data, after the analysis, the value is still fixed or balanced by 2.6%. From these results it can be explained that cash flow from transitor activities reflects cash receipts and disbursements to the Regional Government of Boalemo Regency in government funding.